PEMANFAATAN BONGGOL JAGUNG SEBAGAI BIOETANOL - Suseno, Hadi Prasetyo (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
Indonesian corn production data in 2018 reached 30 million tons, and generally, corncobs have not been utilized. This research is processing corncobs into bioethanol as an effort to exploit the potential of abundant corncobs. The process is carried out in 3 stages, namely hydrolysis with acid (H2SO4 0.5N), fermentation with bread yeast (fermipan), and distillation at 1000C. The study conducted in a three-neck flask equipped with heating, stirring, and turning cooling. The research material used was 40 grams of corncobs powder, H2SO4 0.5N as much as 300 ml, yeast 3 grams, and urea 0.1 gram. The hydrolysis process was carried out using 40gr of corncobs powder, and 0.5N H2SO4 with a volume of 300 ml. Stirring is carried out at 140 rpm rotation with varying time and temperature. Next, the fermentation process is carried out by adding as much as 3 grams of yeast and 0.1 grams of urea. The fermentation process takes 3 days. The distillation process is carried out at a temperature of 1000C with a long time for 2-3 hours. Based on our research, it knows that the time and temperature of hydrolysis affect the ethanol content produced. Optimal addition of yeast at 0.4271% ethanol content is weighing 3 grams. The optimal fermentation time for ethanol content 0.66447% is at the time of fermentation of 3 days.